Policy and Possibilities of Humanitarian Development: Displaced Women and Peace-building Features of the UNHCR. (4th October 2018) - Atkinson, Kelly E
ABSTRACT: Displaced environments are sites of global humanitarian development initiatives that often address how to disrupt cycles of conflict. What ongoing policy initiatives within displaced settings offer opportunities to bolster these humanitarian development initiatives to mitigate conflict dynamics and their impact on displaced populations? This article addresses this question by exploring the role of displaced women in peace-building processes. The focus on women and peace-building has expanded in the 20 years since the United Nations Fourth World Conference on Women, yet the emphasis on displaced women as critical participants in peace-building efforts remains nascent in humanitarian development policy. This proves especially true within the policies of the United Nations High Commissioner for Refugees (UNHCR). Using archival research and interviews with elite professionals, this article evaluates the UNHCR institutional capabilities, limitations, and historic trajectory of its gender policy in order to reveal possibilities for peace-building displaced women within current development policy. Recognising and enabling the peace-building agency of empowered women will posture the UNHCR to implement effective humanitarian development policies to address contemporary global displacement crises, thus strengthening the ongoing United Nations Women, Peace and Security agenda while simultaneously harnessing the peace-building potential of displaced women.